2015
DOI: 10.1128/jvi.03349-14
|View full text |Cite|
|
Sign up to set email alerts
|

The Z Proteins of Pathogenic but Not Nonpathogenic Arenaviruses Inhibit RIG-i-Like Receptor-Dependent Interferon Production

Abstract: Arenavirus pathogens cause a wide spectrum of diseases in humans ranging from central nervous system disease to lethal hemorrhagic fevers with few treatment options. The reason why some arenaviruses can cause severe human diseases while others cannot is unknown. We find that the Z proteins of all known pathogenic arenaviruses, lymphocytic choriomeningitis virus ( IMPORTANCEWe show that all known human-pathogenic arenaviruses share an innate immune suppression mechanism that is based on viral Z protein-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
117
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 56 publications
5
117
1
6
Order By: Relevance
“…Using this approach, we have previously identified differences in the induction of cytokine responses to infection with TCRV or JUNV in macrophages, as well as differences in their influence on host cell apoptosis (Groseth et al, 2011;Wolff et al, 2013a). Other known differences that also might play a role for the virulence include receptor usage (Abraham et al, 2009), as well as the ability to engage in IFN antagonism (Xing et al, 2015). Previous studies have shown that TCRV lacks a novel NP-mediated anti-apoptotic function that was described for JUNV (Wolff et al, 2013a), and together with the observation that TCRV infection also induces severe cytopathic effects (CPEs) during infection in cell culture (Groseth et al, 2011), this suggests that cell death might be due at least in part to apoptotic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, we have previously identified differences in the induction of cytokine responses to infection with TCRV or JUNV in macrophages, as well as differences in their influence on host cell apoptosis (Groseth et al, 2011;Wolff et al, 2013a). Other known differences that also might play a role for the virulence include receptor usage (Abraham et al, 2009), as well as the ability to engage in IFN antagonism (Xing et al, 2015). Previous studies have shown that TCRV lacks a novel NP-mediated anti-apoptotic function that was described for JUNV (Wolff et al, 2013a), and together with the observation that TCRV infection also induces severe cytopathic effects (CPEs) during infection in cell culture (Groseth et al, 2011), this suggests that cell death might be due at least in part to apoptotic responses.…”
Section: Introductionmentioning
confidence: 99%
“…The generally innocuous nature of PICV is also supported by our recent molecular analysis of the viral gene products. We found that the Z proteins of all known human arenavirus pathogens, including the low-risk pathogen LCMV and the highly virulent pathogen Lassa fever virus (LASV), but not those of others such as PICV, can inhibit the RIG-I-like receptors (RLRs) (5). Therefore, we believe that PICV has a better biosafety profile than LCMV, but like LCMV, PICV can induce strong immune responses, especially cellular immunity (19,22).…”
mentioning
confidence: 99%
“…The arenavirus is composed of a total of four genes on two genomic RNA segments in opposite orientations (1). The Z protein, produced from the large (L) genomic segment, is a small RING domain-containing matrix protein that mediates virus budding, regulates viral RNA synthesis, and mediates host immune suppression (4,5). The large L protein (ϳ200 kDa), also encoded on the L segment, is the RNA-dependent RNA polymerase (RdRp), which is required for viral RNA synthesis (6).…”
mentioning
confidence: 99%
“…аналогичным образом первичные макрофаги чело-века показывают более высокий уровень продукции интерлейкина-6, интерлейкина-10 и α-интерферона при инфицировании вирусом такарибе по сравнению с инфицированием патогенным для человека вирусом хунин [7]. показано, что Z-белок всех известных па-тогенных аренавирусов, в отличие от непатогенных, способен ингибировать активацию макрофагов [27]. поскольку макрофаги и дендритные клетки являют-ся антигенпрезентирующими клетками, играющими важную роль в формировании иммунного ответа, ингибирование этих клеток приводит к иммунной супрессии, которая во многом определяет патогенез вирусных геморрагических лихорадок [13].…”
unclassified
“…белок Z патогенных для человека арена-вирусов ингибируют рецепторы, индуцирующие образование интерферона [27]. процесс ингибиро-вания осуществляется в результате взаимодействия N-концевой последовательности белка Z (31 амино-кислотный остаток) и N-концевой последователь-ности соответствующего рецептора, что затрудняет связывание последнего с митохондриальным сиг-нальным белком.…”
unclassified